Skolēnu monologa prasmju pilnveide krievu valodas stundās 1. un 2. klasē - Rabša, Tatjana (Latvijas Universitāte, 2022)
Tatjanas Rabšas diplomdarba temats Skolēnu monologa prasmju pilnveide krievu valodas stundās 1. un 2. klasē. Darbs veltīts 1. un 2. klases skolēnu monologa prasmju līmeņa pilnveidošanai, sasniegumu un problēmu konstatēšanai, grūtību un problēmu cēloņu noteikšanai. Pētījuma mērķis: izpētīt 1. un 2. klases skolēnu monologa prasmju pilnveides didaktiskās iespējas un uzkrāto didaktisko pieredzi zinātnē, ņemot vērā problēmas, kuras konstatētas skolēnu monologa veidošanas prasmēs. Darba gaitā iegūtie dati ļāva noteikt skolēnu monologa prasmju līmeni, noteikt, ar kādām grūtībām sastopas skolēni mācību procesā. Darba autore atlasīja visefektīvākās metodes un paņēmienus, kas vērsti uz sākumskolas skolēnu monologa prasmju pilnveidošanu, kā arī noformulēja galvenās problēmas monologa prasmju attīstīšanai konkrētā klasē. Izpētes rezultāti izmēģinājumu darbībā parādīja, ka skolēniem tika novērota pozitīva dinamika.

The author: Tatjana Rabša Diploma thesis topic: Improvement of monologue skills of 1st and 2nd grade schoolchildren in Russian language lessons. The work is dedicated to the improvement of the level of monologue skills of 1st and 2nd grade schoolchildren, identification of achievements and problems, determination of difficulties and causes of problems. The aim of the research: to study the didactic possibilities of improving the monologue skills of 1st and 2nd grade schoolchildren and the accumulated didactic experience in science, taking into account the problems identified in the students' monologue creation skills. The data obtained in the course of the work allowed to determine the level of schoolchildren' monologue skills, to determine what difficulties students face in the learning process. The author selected the most effective methods and techniques aimed at improving the monologue skills of primary school students, as well as formulated the main problems for the development of monologue skills in a particular form. The results of the research showed that positive dynamics were observed in the schoolchildren. Volume of diploma thesis: is 65 pages, together with appendices 80 pages. The diploma thesis consists of an introduction, 3 chapters, a conclusion, 51 used literature sources, as well as 32 appendices. Keywords: monologue, skills, primary school, methods, techniques.
Improvement of monologue skills of 1st and 2nd grade schoolchildren in Russian language lessons
Keywords: Pedagoģija; monologs; prasmes; sākumskola; metodes; paņēmieni